Seismic analysis of the double-mode radial pulsator SX Phoenicis. Issue 2 (6th October 2020) - Daszyńska-Daszkiewicz, J; Pamyatnykh, A A; Walczak, P; Szewczuk, W
ABSTRACT: We present the results of complex seismic analysis of the prototype star SX Phoenicis. This analysis consists of a simultaneous fitting of the two radial-mode frequencies, the corresponding values of the bolometric flux amplitude (the parameter f ) and of the intrinsic mode amplitude ε. The effects of various parameters as well as the opacity data are examined. With each opacity table it is possible to find seismic models that reproduce the two observed frequencies with masses allowed by evolutionary models appropriate for the observed values of the effective temperature and luminosity. All seismic models are in the post-main sequence phase. The OPAL and OP seismic models are in hydrogen shell-burning phase and the OPLIB seismic model has just finished an overall contraction and starts to burn hydrogen in a shell. The OP and OPLIB models are less likely due to the requirement of high initial hydrogen abundance ( X 0 = 0.75) and too high metallicity ( Z ≈ 0.004) as for a Population II star. The fitting of the parameter f, whose empirical values are derived from multicolour photometric observations, provides constraints on the efficiency of convective transport in the outer layers of the star and on the microturbulent velocity in the atmosphere. Our complex seismic analysis with each opacity data indicates low to moderately efficient convection in the star's envelope, described by the mixing length parameter of αMLT ∈ (0.0, 0.7), and the microturbulent velocity in the atmosphere of about ξt ∈ (4, 8) km s −1 .